Land degradation assessment through an ecosystem services lens: Integrating knowledge and methods in pastoral semi-arid systems. (January 2016) - Tarrasón, D.; Ravera, F.; Reed, M.S.; Dougill, A.J.; Gonzalez, L.
Abstract: This paper develops and applies an integrated and participatory methodological framework to assess land degradation in pastoral systems through an ecosystem services (ES) lens in a semi-arid region of northern Nicaragua. We initially integrated local and scientific knowledge to assess ecological changes and understand the links with ecosystem services supplied by the local grazing system. Hence, we discuss land degradation features and test a state-and-transition ecological model, that is, we developed jointly with local farmers the hypotheses to understand transitions between ecological states and these hypotheses were then evaluated through an inventory of vegetation and an assessment of soil properties and seed bank composition. The assessment reveals that shifts in ecological state do not cause permanent soil properties changes, but that at a landscape scale they can limit production, affecting local livelihoods. The framework proposed provided local farmers with relevant information and facilitated communication with researchers, enabling them to use the co-constructed knowledge to implement adaptive management strategies to improve local productive systems. Highlights: Combination of local and scientific knowledge allows a fine-tuned and rigorous understanding of land degradation processes. Soil properties assessment shows no significant differences between states. Differences between states are observed in seed bank composition. Shifts in vegetation affect productivity and other intangible values and functions provided by the pastoral ecosystem. Ecosystem service focus allows discussing on adaptive management strategies that may directly reverse vegetation shifts.